Source-tracking Klebsiella outbreaks in premature infants using a novel amplicon fingerprinting method - Adam P. Matson; Katrin Unterhauser; Karim Rezaul; Stephanie Lesmes; Yanjiao Zhou; Ian C. Michelow; Naveed Hussain; Mark D. Driscoll (Antimicrobial Resistance and Infection Control)
Abstract Background Even with state-of-the-art infection control practices, premature infants can develop life-threatening infections in the neonatal intensive care unit (NICU). The precise sources of most NICU-associated infections frequently remain unknown and, therefore, are difficult to address. In this study, we used a novel microbiome sequencing approach to source-track lethal sepsis-causing Klebsiella, opportunistic pathogens, and commensal bacterial strains colonizing the gut of hospitalized premature infants. Methods An exploratory-methods, case series was at performed Connecticut Children’s Medical Center NICU in 2021. Long-read 16–23 S rRNA gene sequencing was used to analyze fecal samples, mother’s milk, and clinical bacterial isolates derived from a cluster of Klebsiella-infected, and concurrently hospitalized non-infected, premature infants who were simultaneously enrolled in a neonatal microbiome study. Distinct groups of amplicons comprising a unique fingerprint pattern for a given strain were compared among the samples to ascertain relatedness. Results We confirmed 100% amplicon identity between lethal Klebsiella quasipneumoniae from milk, gut, blood and trachea during sepsis in twins, while differentiating other infecting and colonizing Klebsiella strains in concurrently hospitalized premature infants. The method also successfully discriminated between multiple Klebsiella strains within the gut microbiota of a non-infected infant. Additionally, we showed that human milk is the source of many early intestinal colonizers, including Klebsiella, Enterococcus, Veillonella, and Bifidobacterium strains. Conclusions Amplicon fingerprinting can be utilized as a high-throughput high-resolution test to assist in the investigation of nosocomial outbreaks. Additional applications such as routine monitoring of various reservoirs for potential pathogens could inform infection prevention and control strategies in the NICU.